A Real-time Solar Array Monitoring System Architecture Design Based on FBG. Issue 1 (1st February 2023) - Wang, Yan
Abstract: The solar array is a key part of spacecraft, which is the main power supply. With the trend of spacecraft bus development, the size of the solar array panel attached to the spacecraft becomes larger and larger to provide more load power. Large scale, low stiffness, and flexibility affect the attitude control of the spacecraft directly. Monitoring and analyzing the solar array dynamics behavior will be the key part of the overall design of the spacecraft's control system. The purpose of monitoring is to verify the dynamic modeling and health diagnosis for a typical spacecraft flexible solar array. In this paper, Fiber Bragg Grating transducers (FBGs) and PXI-E Bus technology are used to perform online monitoring of 3D shapes through the strain profile. Using NI DAQ hardware and the FPGA Module to implement a DAQ system that can real-time and accurately perform online analysis and secondary processing of parameters from a system using NI LabVIEW software and RTOS to provide a complete, systematic solution to acquire data from FBGs. In this paper, the design of system architecture is described.